2005
DOI: 10.1111/j.1365-2249.2004.02717.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF-a mediates the development of anaemia in a murine Trypanosoma brucei rhodesiense infection, but not the anaemia associated with a murine Trypanosoma congolense infection

Abstract: SummaryDevelopment of anaemia in inflammatory diseases is cytokine-mediated. Specifically, the levels of tumour necrosis factor-a a a a (TNF-a a a a ), produced by activated macrophages, are correlated with severity of disease and anaemia in infections and chronic disease. In African trypanosomiasis, anaemia develops very early in infection around the time when parasites become detectable in the blood. Since the anaemia persists after the first waves of parasitaemia when low numbers of trypanosomes are circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 26 publications
(26 reference statements)
3
64
2
Order By: Relevance
“…In T. congolense infections, TNF-deficient mice present severely shortened survival times and fail to control the first parasitaemia peak [14,15,34]. A recent study involving iNOS À/À (inducible nitric oxide synthase-deficient), TNF À/À , TNF-R(receptor)1 À/À and TNF-R2 À/À mice confirmed that TNF and NO cooperate in controlling T. congolense [15].…”
Section: Tnf and Nitric Oxide: The Double Agentsmentioning
confidence: 73%
See 1 more Smart Citation
“…In T. congolense infections, TNF-deficient mice present severely shortened survival times and fail to control the first parasitaemia peak [14,15,34]. A recent study involving iNOS À/À (inducible nitric oxide synthase-deficient), TNF À/À , TNF-R(receptor)1 À/À and TNF-R2 À/À mice confirmed that TNF and NO cooperate in controlling T. congolense [15].…”
Section: Tnf and Nitric Oxide: The Double Agentsmentioning
confidence: 73%
“…brucei and T.b. rhodesiense infection [7,34,41,42]. However, the direct effector function of TNF on trypanosomes is only confirmed in a limited number of T. brucei strains and is not a general operating mechanism [43].…”
Section: Tnf and Nitric Oxide: The Double Agentsmentioning
confidence: 99%
“…The mean TEC, PCV and Hb reduced significantly (P<0.01) compared to control group, indicating anemia. The patho physiology of anaemia in Trypanosomiasis is complex and multi factorial in origin [7]. It initiates a cascade of events leading to haemolytic anaemia and cardiovascular collapse [8].…”
Section: Resultsmentioning
confidence: 99%
“…This product is known to lyse red blood cells in the absence of antibodies (in-vitro) and haemodilution (in-vivo). This mechanism has been adequately described in gold fish (Carassius auratus) infected with Trypanosoma dahilewskyi (Nazrul-Islam and Woo, 1991) and in murine models infected with T. b. rhodesiense (Naessens et al, 2005 …”
Section: Introductionmentioning
confidence: 97%
“…The T. brucei group of trypanosomes (T. brucei, T. b. gambiense, T. b. rhodesianse and T. evansi) mostly invade tissues (humoral) whereas, T. congolense and to a lesser extent T. vivax and T. cruzi predominantly restrict themselves to the blood circulation (haemic) (Igbokwe, 1994;. The mechanism or pathophysiology of anaemia in trypanosomosis is complex and multifactorial in origin (Naessens et al, 2005). It initiates a cascade of events leading to haemolytic anaemia and cardiovascular collapse (Anosa, 1988).…”
Section: Introductionmentioning
confidence: 99%